Understanding and Control of High Temperature Oxidation Flaws of Low-Density Poly(ethylene) with Raman Spectroscopy. (5th June 2014) - Veitmann, Marie; Jumeau, Richard; Bourson, Patrice; Ferriol, Michel; Lahure, François
Abstract : Studies of high temperature oxidation of polyethylene are not much present in the literature though it can really be a problem especially in polymer production and processing. This study aims to detect oxidation flaws in polyethylene and to determine their impact on polymer structure and properties. Besides, we suggest a method via PLS-regression to determine the degree of flaws that can occur during polymer processing due to oxidation. Several kinds of oxidation flaws were reproduced in laboratory at 150°C in an oven operating in air and Raman spectroscopy analysis was performed on each sample. Using statistical tools as chemometrics on these spectra, we have built a Partial Least Square (PLS) model able to predict the oxidation degree of flaws. Interpretation of the model construction and further characterization tests show that oxidation can be followed with the evolution of the crystalline carbon group and of the created carbonyl functions. Finally we suggest possible mechanisms which can explain the high temperature oxidation process in LPDE, and we link them to the modification of the material properties.